Treatment goals for moderate to severe psoriasis: An Australian consensus. (18th January 2013) - Baker, Christopher; Mack, Alexandra; Cooper, Alan; Fischer, Gayle; Shumack, Stephen; Sidhu, Shireen; Soyer, Peter; Wu, Jason; Chan, Jonathan; Nash, Peter; Rawlin, Morton; Radulski, Barbara; et al.
Abstract Background/Objectives The high incidence of comorbidities in patients with psoriasis, significant impact on quality of life and patients' dissatisfaction with treatment led a European group to develop a consensus position on psoriasis treatment goals. There is an evident need for similar treatment goals in Australia. The aim of this project was to develop Australian treatment goals that reflect the local environment. Methods A panel of 12 representatives was drawn from across Australia consisting of nine dermatologists and a rheumatologist, a dermatology nurse and a general practitioner (GP)/dermatology trainee. The group met on three occasions between September 2011 and March 2012. The panel undertook a literature review and critically examined available evidence‐based treatment goals. A questionnaire relating to psoriasis assessment and specific treatment outcomes was developed. Following discussion and debate, recommended treatment goals for psoriasis patients in Australia were determined. Results The panel agreed by consensus on recommended psoriasis treatment goals in the Australian environment. There was recognition that in addition to psoriasis area severity index (PASI) assessment, a quality of life assessment was highly relevant in determining psoriasis severity and treatment outcome. Mild psoriasis was defined as PASI ≤ 10 and a dermatology life quality index (DLQI) ≤ 10, with moderate to severe psoriasis defined as PASI > 10 and/or DLQI > 10. The presence of certain definedclinical features would elevate a patient's classification from mild to moderate/severe. The target for treatment was defined as a maintained change in PASI ≥ 75% improvement and DLQI ≤ 5. These largely concurred with the European treatment goals. A flow chart for psoriasis management in Australia based on outcome measures was developed. Conclusions There is a need to identify and articulate treatment goals for psoriasis. Assessment of psoriasis severity requires both physical scoring (PASI) and consideration of quality of life measures (DLQI). Identification of treatment goals will guide clinicians in treatment decision‐making, enhance the availability and appropriate use of therapies and increase patient satisfaction with their care.